2023
DOI: 10.1177/15589250221137897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using alternate elastic and non-elastic yarns in warp on shrinkage and stretch behavior of bi-stretch woven fabrics

Abstract: Stretch woven fabrics are known for their elastic and recovery properties. To date, they found many interesting applications from simple jeans to complex fabric structures with functional properties for example bi-stretch auxetic woven fabrics, compressions garments and stretchable textile carriers for healthcare applications. Many studies have been carried out on the physical, mechanical and comfort properties of stretchable knitted and woven fabrics. However, to identify combination of yarns with different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cotton is a non-allergenic fiber and does not cause skin irritation. Hence, cotton-wrapped elastic core-spun yarns have been used to produce stretchable and adaptable garments for patients, compression garments and bandages, medical braces, and other therapeutic textiles [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cotton is a non-allergenic fiber and does not cause skin irritation. Hence, cotton-wrapped elastic core-spun yarns have been used to produce stretchable and adaptable garments for patients, compression garments and bandages, medical braces, and other therapeutic textiles [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the production of stretchable and comfortable apparel for patients, stretchable yarns (core spun) have been used [ 6 ]. To produce triaxial and biaxial auxetic fabrics (woven), stretchable yarns have been used [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that elastic yarns exhibited higher shrinkage and a new parameter was introduced to understand fabric comfort. 15…”
Section: Introductionmentioning
confidence: 99%
“…It was found that elastic yarns exhibited higher shrinkage and a new parameter was introduced to understand fabric comfort. 15 Sustainable generation in textiles is a significant topic, and new generation regenerated cellulose fibers significantly improve sustainability. One of the aims of this study was to examine the effect of Naia™ fibers obtained by acidifying cellulose raw materials obtained from wood and cotton fibers on the thermal and hand features of the denim fabric structure.…”
Section: Introductionmentioning
confidence: 99%